(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2022)
This research aimed to analyze the impact of Google Classroom assisted by Google Meet use on the interests and learning outcomes of students’ mathematics Class V Kristen Elementary School. This type of research was quantitative research with quasi-experiment. The research design used was a non-equivalent control group design. The population in this study were the students of class V of Kristen Elementary School IPEKA Makassar, with a total of 60 students divided into two classes, VA and VB. Va class was the experimental class, and VB class was the control class. The technique of data collection was using tests and learning interests. Data analysis techniques in research used descriptive and inferential statistical analysis. Based on the data analysis, the average learning interest of experimental class students was 73.33, and control classes were 59.33. In addition, classically the interest in learning experimental classes reached 80%. The average results of experimental math learning classes were 93 while the average results of learning math control classes were 69.67. In addition, the completion of classical learning experimental classes reached 100%. The N-Gain Test obtained a coefficient of 0.841 and was categorized as high. Test the hypothesis using an independent sample t-test. In statistical analysis, learning interests were obtained sig value. (2-tailed) = 0.00 < 0.05. In the analysis of post-test results of learning results obtained Sig values. (2-tailed) = 0.032 < 0.05. From the data, it can be concluded that the use of Google Meet assisted by Google Classroom affected the interests and results of learning mathematics students of class V Kristen Elementary School IPEKA Makassar.